Procedural Norms in de gravioribus delictis regulation of 2010 - Sánchez-Girón Renedo, S.J., José Luis (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The norms of the year 2010 about delicts reserved to the CDF integrate numerous concessions granted by the Pope to this dicastery after the norms of the year 2001 about the same matter. The procedural peculiarities for these delicts are mainly the necessary sending to the CDF by the Ordinary the investigation he may carry out at the news of a delict, the possibility to follow, according to the decision of the CDF, a procedural way judicial or administrative (this even to impose the expulsion from the clerical state), the exclusive competence of the CDF for the second instance and the possibility to adopt the precautionary measures of canon 1722 even during the investigation stage.
Keywords: criminal action; prescription; preliminary investigation; judicial procedure; administrative procedure; precautionary measures